Relativity: chronoeometric drawings - I. O. Sazonenko; V. . I. Sazonenko (Литьë и металлургия)
Based on the simplest representations, questions of relativistic compactification of reference systems with relative virtual motion, non-locality of pseudo-reference frames of world constants and Schrödinger’s thesis on the completeness of the general and incompleteness of the particular are considered.